2006
DOI: 10.1007/s00167-005-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of delayed gadolinium-enhanced MRI (dGEMRIC) for qualitative evaluation of articular cartilage of patellofemoral joint

Abstract: Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) was used for the measurement of relative proteoglycan depletion of articular cartilage in the patellofemoral (PF) joint following a proprietary protocol, which was compared with the X-ray images, proton density weighted MR images (PDWI) and arthroscopic findings. The study examined 30 knees. The ages ranged from 16 to 74 (average 40.3) years. The Gd-DTPA(2-)containing contrast medium was used in a single dose. The subjects were made to exercise the knee jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…The diagnosis of damage in articular cartilage was possible in all 16 cases with radiographic KLG 1 on dGEMRIC, while the intensity changes were not found in 10 of 16 cases on Proton density Weighted Image (PDWI) 33 .…”
Section: Resultsmentioning
confidence: 96%
“…The diagnosis of damage in articular cartilage was possible in all 16 cases with radiographic KLG 1 on dGEMRIC, while the intensity changes were not found in 10 of 16 cases on Proton density Weighted Image (PDWI) 33 .…”
Section: Resultsmentioning
confidence: 96%
“…The abstracts of all 1879 studies were reviewed and 52 articles met the pre-determined inclusion and exclusion criteria. Fourteen level I, 7, 14, 16, 17, 27, 37, 4043, 50, 72, 84, 85 13 level II 4, 10, 26, 28, 38, 39, 47, 55, 59, 74, 78, 80, 90 and 26 level III–V 5, 8, 12, 23, 29, 3133, 35, 36, 44, 48, 49, 54, 60, 6365, 69, 75, 8183, 86, 93 studies were identified. For level I and II studies, Table 2 describes the breakdown of the number of articles that reported results regarding diagnostic performance of MRI compared to arthroscopy for grading of chondral involvement, reliability of grading between evaluators, MRI sequence performance, and involved articular cartilage surface or knee compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, T 1,Gd is lower with preradiographic damage [47] and with radiographic cartilage damage and OA [43,46,48] when compared with healthy joints. T 1,Gd also correlates with radiographic scores of OA [43,44], joint alignment [43,45,101] and measures of joint pain [45]. Additionally, dGEMRIC has been shown to be sensitive to pre-radiographic damage [49].…”
Section: T 1 Mapping and Delayed Gadolinium-enhanced Magnetic Resonanmentioning
confidence: 98%
“…A significant thrust in much of the qMRI literature is towards the correlation of various qMRI values to biochemical content, typically determined in explants through histology [14,26 -30,41,42,50-52,107], and to pain score or OA grade [39,43,44,48,54,56,57,90,126]. A number of groups have applied qMRI techniques to evaluate the differences between cartilage in normal subjects and patients with higher OA risk [43 -45,87,101].…”
Section: Shifting the Paradigm Towards Diagnosis Of Osteoarthritis Inmentioning
confidence: 99%